EFFECT OF THE KEPEL LEAVES EXTRACT (STELECHOCARPUS BURAHOL [BL.] HOOK. F. & TH.) ON SPRAGUE-DAWLEY RATS: AN ACUTE TOXICITY STUDY - Purwantiningsih; Nurlaila (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The aim of this study was to evaluate the acute effect of the Kepel leaves extract (Stelechocarpus burahol [Bl.] Hook. F. and Th.) after a single dose oral treatment on the body weight and the organ of Sprague-Dawley (SD) rats. Methods: This experiment was conducted based on the OECD-guideline 401-1999. A single oral dose of the Kepel leaves ethanol extract (0, 200, 585, 1711, and 5000 mg/kg body weight) were given to male and female SD rats (each group, n=6). The control group was only given the vehicle (olive oil). The observation was done during 24 hrs and was continued until 14 days, because there was no death among the tested animals, included the recording of the death of animal test, body weight, toxic signs, duration, and reversibility of the toxic effect. A half of the rats in each group were sacrificed after 24 hrs observation, and remain of the animals were sacrificed after 14 days observation. The seven organs (kidney, lung, liver, spleen, intestine, stomach, and heart) were taken from each animal for macroscopic and microscopic (histopathology) examination. Results: The results showed that the acute toxicity potency of the ethanol extract of Kepel leaves was practically non-toxic, and the pseudo-lethal dose of 50% (pseudo-LD 50 ) value was higher than 5000 mg/kg body weight. Conclusion: Based on the macroscopic and microscopic observation, it could be concluded that the ethanol extract of Kepel leaves did not induce the toxic effect on the body weight and the organ of male and female SD rats. Keywords: Stelechocarpus burahol (Bl.) Hook. F. and Th., Acute toxicity study, Body weight, Organ, Sprague-Dawley rat.